The Influence of Preceptorship Program in Clinical Practice toward Student Satisfaction - Heru Supriyanto; Nurhidajah - (Universitas Muhammadiyah Semarang, 2011)
Bachground - Preceptorship is one of clinical teaching method which involves one to one relationship. This method enables nursing students to have optimal guidance during transfer of knowledge, skill and professional concept. Literature shows that preceptorship program provides some advantages for the nursing students practicing in clinical area in relation to increase their competencies. However, it is very rare that this method is applied in Indonesia. Objeetive-This study aimed to examine nursing students' satisfaction with the development of preceptorship program in the clinical practice. Method - A quasi experimental with static group comparison design was used in this study compromised 80 samples divided into control and treatment group. Result - The result of the study indicated that there was statistical significance in treatment group related to the students' satisfaction (t=0.000, p<0.005). Recommendation - Based on the result, It is recommended that the implementation of preceptorship program in clinical practice should be considered. Key words - Preceptorship, Students' Satisfaction